Maternal Peer Support Through a Caregroup Model Improves Complementary Feeding of Infants by Refugee Mothers in Post-Emergency Settlements in the West-Nile Region in Uganda. (14th June 2022) - Komakech, Joel; Rakotomanana, Hasina; Walters, Christine; Kabahenda, Margaret; Cole, Ki; Emerson, Sam; Hildebrand, Deana; Stoecker, Barbara
Abstract: Objectives: Introduction: Infant complementary feeding in refugee settlements remains inadequate, amidst declining humanitarian aid. However, there is limited evidence for interventions to address these nutrition challenges in the refugee settlements. Objective: Examine the effects of peer-led integrated nutrition education on infant feeding by South Sudanese refugee mothers in the West-Nile region in Uganda. Methods: A community-based randomized control study enrolled 390 pregnant mothers in the 3 rd trimester as baseline for a peer-led nutrition education intervention using the caregroup model. Two groups (moms-only and moms & dads combined) comprised treatments with a control group. Higher scores on the Medical Outcomes Study (MOS) Social Support Index were used as a proxy for better maternal social support. Infant complementary feeding was assessed using the 2021 WHO guidelines. Multivariable logistic regression models determined effects of the interaction of maternal social support by group over time on infant feeding practices. The models were adjusted for maternal and infant confounders. Results: Maternal age (mean ± SD) was 27.7 ± 5.1 years while the infant birthweight was 3.1 ± 0.5 kg. Higher maternal social support positively affected timely introduction of solid and semi-solid foods in moms-only ( β = 0.11, p = .011) and moms & dads ( β = 0.11, p = .001) groups. Positive intervention effects were noted on infant minimum dietary diversity for both the moms-only group ( β = 0.06, p = .01) and the moms & dads group ( β = 0.03, p = .001), but no effect was observed between maternal social support and infant minimum meal frequency. However, higher maternal social support in both moms-only and moms & dads groups influenced meeting the minimum acceptable diet ( β = 0.07, p = .016 and β = 0.04, p = .026 respectively) and consumption of eggs and/or flesh foods ( β = 0.11, p < .0001 and β = 0.05, p = .004). Conclusions: A maternal peer support integrated nutrition education program improved complementary feeding of infants in post-emergency settlements. Enhanced maternal social support in nutrition-sensitive programs may benefit infants in post-emergency settlements in the West-Nile region in Uganda. Funding Sources: A grant from the Nestlé Foundation for the Study of Problems of Nutrition in the World, Switzerland.